Allergic Rhinitis in Children: Principles of Early Diagnosis and Effective Therapy. Overview of Clinical Recommendations - Alexander A. Baranov; Leyla S. Namazova-Baranova; Rakhim M. Khaitov; Nataliya I. Ilyina; Oksana M. Kurbacheva; Gennadii A. Novik; Fedor I. Petrovsky; Elena A. Vishneva; Anna A. Alekseeva; Liliya R. Selimzyanova (Педиатрическая фармакология)
The article briefly summarizes the key provisions of the clinical recommendations on medical care delivery for children with allergic rhinitis: modern approaches to diagnosis and therapy. The current document was developed by the professional association of pediatric specialists —the Union of Pediatricians of Russia — together with the leading experts of the Russian Association of Allergists and Clinical Immunologists. The recommendations are regularly updated due to the latest evidence-based results of effectiveness and safety of various medical interventions. The article presents information on the epidemiology of allergic rhinitis in children, specific diagnostic features which provide the opportunity for the timely and correct diagnosis and an effective therapy with personal approach.